ANALISIS TEKNO EKONOMI ATAP SURYA STUDI KASUS DI KOTA MEDAN, INDONESIA - Nababan, Wilson Sabastian; Sihombing, Suriady; Peranginangin, Siwan Ediamanta; Napitupulu, Richard A.M (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2023)
Indonesia has released its pledge on reducing Greenhouse Gas (GHG) emissions. Mitigation measures include increasing the use of renewable energy. Solar roofs are one potential mitigation measure to meet GHG emission reduction and renewable energy targets. As more attention is being focused on developing this renewable energy resource globally, the technical and economic assessment of this resource is critical to ascertain its feasibility. In this study, a technological and economic analysis of solar roof tops is presented. The analysis was carried out based on solar irradiation in the city of Medan, Indonesia. Solar irradiation over several days was measured. The measured data and the solar photovoltaic module panels available in the Indonesian market are used to carry out the technical analysis. Based on the technical analysis and economic analysis carried out, the economic analysis of the results of the visualization of the power produced by the PV system which was carried out for 1 year resulted in a total value of electricity of IDR 3,672,895 for the city of Medan. It is expected to provide the necessary information to build cities with low emissions. Keywords: Solar Roof, Photovoltaics, Technoeconomics